Does engaging with an interactive adherence intervention improve time in therapeutic range compared to receiving an education intervention alone, among patients anticoagulated with warfarin in Cape Town, South Africa? - Pillay, Chriselda (Department of Public Health and Family Medicine, 2025)
Background: Warfarin is the mainstay of oral anticoagulation in South Africa. There is wide variability between individual dose requirements. Regular International Normalised Ratio (INR) monitoring to guide dosing is required. Maintaining INR in therapeutic range is important for efficacy and safety. Time in Therapeutic Range (TTR) ≥65% is associated with better outcomes. The WarPATH study included an adherence intervention comprising patient education sessions and weekly interactive text messages with clinician contact details. We hypothesised that engaging with the interactive component of the intervention would improve TTR. Objectives: To identify predictors of higher TTR, to compare retention in INR monitoring between those who did and did not engage with the interactive component of the adherence intervention and to describe the content of those interactions. Methods: This analysis is nested in the WarPATH study, and we included South African WarPATH participants with sufficient INR results to calculate TTR (by Rosendaal method) in weeks 2-12 following warfarin initiation. We constructed a multivariable linear regression model to identify associations with higher TTR. We constructed a logistic regression model of associations with retention in INR monitoring in months four to seven following warfarin initiation (≥3 INR results, or documented warfarin stop by clinician between four and seven months if <3 INRs) Results: We included 61 participants, 51% men, median age 50 years (Inter-quartile range (IQR) 43-61). Median TTR was 40% (IQR 28-64%), only 14 (23%) achieved TTR≥65%. In a multivariable linear regression model, male sex (p= 0.04) and older age (p=0.02) were associated with higher TTR; adjusted for mobile phone ownership, anticoagulation indication and engagement with the interactive component of the adherence intervention. In 47% of telephonic interactions, participants requested assistance with systems challenges to anticoagulation care. Although TTR was not associated with engagement, in a multivariable logistic regression model (n=57), participants who engaged with the interactive component of the intervention were more likely to be retained in INR monitoring (Adjusted Odds Ratio 4.8, 95% Confidence Interval 1.32-21.1, p=0.02), adjusted for sex, age, anticoagulation indication, mobile phone ownership. Conclusion: Anticoagulation control in this cohort was poor. Participants who engaged with the interactive intervention were more likely to be retained in INR monitoring. Interaction content revealed multiple health system barriers to good anticoagulation control on warfarin. This adherence intervention is simple and scaling for public sector implementation should be explored alongside access to alternative oral anticoagulants requiring no laboratory monitoring or individualised dosing